2019
DOI: 10.1111/gcbb.12661
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term growth response of jack pine and spruce spp. to wood ash amendment across Canada

Abstract: Wood ash amendment to forest soils contributes to the sustainability of the growing bioenergy industry, not only through decreased wood ash waste disposal in landfills but also by increasing soil/site productivity and tree growth. However, tree growth studies to date have reported variable responses to wood ash, highlighting the need to identify proper application rates under various soil/site conditions to maximize their benefits. We explored the influence of tree species, wood ash nutrient application rates,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…Our results are consistent with the findings of Emilson et al (2020) in regard to jack pine and white spruce. This Canadawide study revealed that the relationship between short-term response of jack pine and application rates is relatively linear.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our results are consistent with the findings of Emilson et al (2020) in regard to jack pine and white spruce. This Canadawide study revealed that the relationship between short-term response of jack pine and application rates is relatively linear.…”
Section: Discussionsupporting
confidence: 92%
“…Brais et al (2015) reported decreased growth of black spruce starting at 4 dry Mg ha -1 (same ash as in our study). Emilson et al (2020) also reported a general negative growth response of black spruce to ash application using the Canadian AshNet database, whereas Staples & Van Rees (2001) and Bieser & Thomas (2019) observed a negative response of white spruce to wood ash. Salt and metal toxicities were believed to be the cause for the decline in growth of black and white spruce.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tree species also vary widely in responses to amendments of wood charcoals (Pluchon et al, 2014;Thomas & Gale, 2015), and wood ash (Emilson et al, 2020). Fire-adapted species, including P. banksiana, might be expected to show the most significant positive responses to fire residues.…”
Section: Discussionmentioning
confidence: 99%